Writing-to-learn in biology and mathematics teacher education: promoting students’ topic knowledge and insight - Van Dijk, Aartje; Van Gelderen, Amos; Kuiken, Folkert (Frontiers in Education, 2023)
In the present study, effects of Genre Writing instruction added with planning and revising activities (GWPR) are investigated in teacher education. This type of instruction was considered promising because it appeared to lead to positive effects on topic knowledge and insight in previous studies conducted in secondary education. Researchers’ expectation was that writing-to-learn activities by means of GWPR support teacher candidates in acquiring topic knowledge and insight into subject matter. Two studies were undertaken, one in biology and one in mathematics teacher education, each comprising a quasi-experiment and a think-aloud study. Both studies were embedded in regular courses. Researchers co-created writing-to-learn tasks with the teacher educators involved. Both experiments showed positive effects on learning. Results of the think aloud studies provided evidence for specific indicators (students’ reflections) of the process of writing-to-learn, in which experimental teacher candidates differed from the control group.